PENGARUH MOTIVASI DAN PENGALAMAN KERJA TERHADAP PRODUKTIVITAS PEGAWAI PUSKESMAS LEMPAKE SAMARINDA - Mardiana, Seri Nornaningsih, H. Eddy Soegiarto K (EKONOMIA, 2015)
With Human Resources planning through mature, work productivity of the existing workforce can be improved. Motivation and good work experience can also support the success of an organization in achieving its goals. The research objective was to determine the effect of motivation and work experience on the productivity of employees at Puskesmas Lempake Samarinda. This thesis discusses how the influence of motivation and work experience of the employee productivity lempake health centers. Data obtained through questionnaires by distributing questionnaires to 44 (forty-four) employees Puskesmas Lempake. Results of this research study showed that motivation variable (X1) and work experience variable (X2) positive and significant impact on employee productivity Puskesmas Lempake variable (Y). By Fhitung 9,408> F table 3.23. Regression analysis results showed a positive and significant influence between motivation (X1) to employee productivity (Y) partially with thitung of 2,239> t table 1,682 and significance 0.031 <0.05. Work experience (X2) in this study has a positive and significant impact on employee productivity (Y) partially due to the 2,655 thitung> t table 1,682 and 0,011 significance <0.05.